2022
DOI: 10.1007/s10113-022-01987-z
|View full text |Cite
|
Sign up to set email alerts
|

European beewolf (Philanthus triangulum) will expand its geographic range as a result of climate warming

Abstract: Climate change is an important driver of the spread of apiary pests and honeybee predators. These impact on one of the economically most important pollinators and thus pose serious threats to the functioning of both natural ecosystems and crops. We investigated the impact of the predicted climate change in the periods 2040–2060 and 2060–2080 on the potential distribution of the European beewolf Philanthus triangulum, a specialized honeybee predator. We modelled its potential distribution using the MaxEnt metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 93 publications
0
4
1
Order By: Relevance
“…In addition, emission scenarios generated less uncertainty in predicting potential distributions than GCMs ( Figure 4 and Figure 5 ). Our findings were inconsistent with previous studies in that the uncertainty caused by emission scenarios was greater than that caused by GCM [ 37 , 38 , 39 ]. The reason for the difference may be the different emission scenarios chosen.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, emission scenarios generated less uncertainty in predicting potential distributions than GCMs ( Figure 4 and Figure 5 ). Our findings were inconsistent with previous studies in that the uncertainty caused by emission scenarios was greater than that caused by GCM [ 37 , 38 , 39 ]. The reason for the difference may be the different emission scenarios chosen.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have shown that being dependent on only one SDM to predict the potential distribution of species would cause the result deviation problem [ 35 , 36 ]. In addition, studies have shown that different global circulation models (GCMs) will bring uncertainty to SDMs prediction [ 37 , 38 , 39 ], but the uncertainty caused by emission scenarios is significantly higher than that caused by GCMs [ 37 ]. Therefore, the reliability of conservation studies for endangered species could be improved by considering the comprehensive results under the influence of various uncertainties, including SDM algorithms, emission scenarios and GCMs.…”
Section: Introductionmentioning
confidence: 99%
“…As a second-generation empirical niche model, the integrated Maxent modeling we developed has partially considered the changing responses of disease transmission to complex future conditions (Peterson, 2014). (Anibaba et al, 2022;Olszewski et al, 2022;Puchałka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…If only one of them is used, the results are possibly biased. A better selection of GCMs should be calculating the average and standard deviation of several representative GCMs (e.g., low change level: HadGEM2‐ES; moderate change level: IPSL‐CM5A‐LR; high change level: MPI‐SM‐LR) (Anibaba et al, 2022; Olszewski et al, 2022; Puchałka et al, 2021). In this study, we selected the BCC‐CSM1‐1 model developed by Beijing Climate Center, China Meteorological Administration.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our experiences. Olszewski et al [82] reported the increase in population density of Philanthus triangulum (Fabricius, 1775), and Eickermann et al [83] wrote about the increasing population of Polistes spp. in Europe.…”
Section: Aculeatamentioning
confidence: 99%